1997
DOI: 10.1021/ma961165o
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization in Microemulsions with Polymerizable Cosurfactants:  A Route to Highly Functionalized Nanoparticles

Abstract: The polymerization of styrene-in-water microemulsions prepared using polymerizable cosurfactants, such as hydroxyalkyl acrylates or methacrylates, gives rise to stable suspensions of well-defined highly functionalized nanoparticles in the 15−25 nm diameter range. Among the various associations of ionic surfactants with hydroxyalkyl (meth)acrylate cosurfactants tested, the surfactant/cosurfactant system (sodium dodecyl sulfate/2-hydroxypropyl methacrylate) is found to be the most effective and allows the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 23 publications
1
53
0
1
Order By: Relevance
“…Microemulsion polymerization yields stable latexes in the nanosize range (a 50 nm) that find applications in drug delivery, microencapsulation and biomedical diagnosis [156][157][158]. Most of these applications require highly functionalized particles, which have been prepared by using a second monomer bearing the desired functionality [159].…”
Section: Microemulsion Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microemulsion polymerization yields stable latexes in the nanosize range (a 50 nm) that find applications in drug delivery, microencapsulation and biomedical diagnosis [156][157][158]. Most of these applications require highly functionalized particles, which have been prepared by using a second monomer bearing the desired functionality [159].…”
Section: Microemulsion Polymerizationmentioning
confidence: 99%
“…Most of these applications require highly functionalized particles, which have been prepared by using a second monomer bearing the desired functionality [159]. Larpent et al [160,161] reported on the use of polymerizable cosurfactants to produce highly functionalized nanoparticles. It should be pointed out that although these cosurfactants help lowering the interfacial tension of the system, they are not true surfactants in the sense that they cannot emulsify two nonmiscible phases.…”
Section: Microemulsion Polymerizationmentioning
confidence: 99%
“…[29] The aqueous suspension of chlorobenzyl-functionalized crosslinked polymer nanoparticles, the nanolatex NL-CH 2 Cl, was obtained by the copolymerization of styrene, vinyl benzyl chloride, and hydroxypropyl methacrylate (cosurfactant) in an oil-in-water microemulsion stabilized with an anionic surfactant (sodium dodecyl sulfate, SDS). [31] We chose an anionic surfactant stabilizer rather than a cationic one in order to i) limit the competitive hydrolysis of the chlorobenzyl surface end-groups, [9] and ii) avoid any electrostatic attraction and further self-assembly with the heteropolyanion or the final negatively charged hybrid nanoparticles. The grafting is readily performed in water at room temperature by adding POM-SH to the as-prepared nanolatex NL-CH 2 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…Reactive Nanoparticles, NL-CH 2 Cl: The starting aqueous suspension of chlorobenzyl-functionalized nanoparticles, i.e., the nanolatex NL-CH 2 Cl, was prepared using a previously described procedure [31]. A mixture of monomers (styrene, chloromethylstyrene, vinyl benzyl chloride (VBCl), and divinyl benzene (DVB) as crosslinking agent) in an oil-in-water microemulsion that was stabilized by a mixture of a polymerizable cosurfactant (hydroxypropyl methacrylate, HPMA) and an anionic surfactant (SDS) were polymerized.…”
Section: Methodsmentioning
confidence: 99%
“…Sa povećanjem koncentracije TMEDA zapaţa se isti trend za vrednosti prinosa i efikasnosti kalemljenja kao i kod KPS-a. Sistem APS-tetrametildiaminometan se upotrebljen je za polimerizaciju stirena u mikroemulziji [272]. Stepen konverzije monomera od 100 % dostignut je za 2 h na temperaturi od 25 0 C u mikroemulziji SDS/1-pentanol.…”
Section: Slika 114 Mehanizam Iniijacije Sistema Aps -3' Diaminunclassified